Inequality, continuity and change: Andy Furlong's legacy for youth studies. (2nd January 2020) - Woodman, Dan; Shildrick, Tracy; MacDonald, Robert
ABSTRACT: This article introduces a special issue of the Journal of Youth Studies, dedicated to Professor Andy Furlong, the Journal's founding Editor. The central questions that drove Andy Furlong's scholarship were the relationship between continuity and change in young people's lives and about the place of youth in the reproduction of inequality across generations. These questions have been central to the wider field of Youth Studies that he helped to build. His work provided a powerful example of how to engage with these questions with a strong sense of social justice but the answers he gave, as with all such answers in sociology, are necessarily provisional. The articles collected in this issue bring empirical research and new concepts that build on this legacy, suggesting new ways to capture the experiences of young people across the multiple spheres of their lives and how disadvantage and inequality are made in the context of processes across time.